Metalloenzymes in denitrification applications and environmental impacts - Moura, Isabel; Moura, José J.G; Pauleta, Sofia R.; Maia, Luisa B. (RSC metallobiology series, 2017)
comprehensive and unified picture of the denitrification process is presented and discussed by recognised specialists in the field in this book. An important topic in many biological, environmental and agricultural contexts, this book will aid teaching and help bioinorganic chemists and biotechnologists gain an up-to-date picture of the science behind the denitrification process. The book covers the key metalloenzymes, including their structures, functions and mechanisms. It also explains novel methodologies for monitoring denitrification in vivo, biotechnological methods for water treatment, and modelling and mitigating negative environmental impacts of denitrification